Determination of crystal size distributions in alumina ceramics by a novel X‐ray diffraction procedure. Issue 3 (15th November 2017) - Neher, Sigmund H.; Klein, Helmut; Kuhs, Werner F.
Abstract: A novel X‐ray diffraction based method is presented, capable of determining volume‐based crystal size distribution (CSD) of polycrystalline materials and crystalline powders with unprecedented sampling statistics; the method is named fast X‐ray diffraction crystal size distribution analysis (FXD‐CSD). FXD‐CSD can be performed with standard laboratory X‐ray diffractometers equipped with a position sensitive detector and uses a software package written in Python for the data analysis. FXD‐CSD is a destruction‐free and generally applicable method to establish CSDs of polycrystalline materials as well as powders for sizes well below 1 μm up to about 100 μm; it even allows for studies of samples enclosed in complex environments, e.g., for in situ measurements in a furnace or in a pressure cell. To show the capability of the method the microstructural evolution of four alumina substrates with different time‐spans of sintering (4, 8, 16, and 24 hour at 1600°C) is investigated via FXD‐CSD and SEM imaging. The corresponding CSDs and average grain sizes are determined, results obtained by FXD‐CSD and the line‐intersection methods are compared and clear evidence for the presence of abnormal grain growth (AGG) during sintering is shown. From three tested probability density functions (PDF) describing the CSDs a log‐normal PDF fits best to the volume based CSDs; the method provides size distributions with unprecedented precision opening the way to a systematic and meaningful comparison between theoretically predicted and observed CSDs.